In Situ Investigation of Adhesion Mechanisms on Complex Microstructured Biological Surfaces. Issue 20 (26th August 2020) - Kumar, Charchit; Favier, Damien; Speck, Thomas; Le Houérou, Vincent
Abstract: Recently, plant surfaces have attracted attention given their fascinating functionalities, particularly adhesive properties, which largely result from their diverse surface structuring. This paper contributes to the adhesion mechanics investigation on complex biological surface morphologies. Elastomeric replica of three different plant leaves, comprising morphologies at a broad scale (0.5–100 µm), with distinct shapes and complexity, and of a smooth surface are studied in contact with an adhesive probe. To perform precise adhesion measurements, an ultra‐nanoindenter is modified based on the Johnson–Kendall–Roberts (JKR) mechanics and equipped with an in situ real‐contact visualization system. The adhesion force on all surfaces is systematically investigated regarding the preload conditions. The results are analyzed in the light of Hertzian and JKR theories, and underlying morphology‐specific mechanisms are identified. A close examination of contact image–force reveals attachment–detachment mechanisms, arising from different preloads and topographies. A significant influence of preload on adhesion is observed on the surface with fine microstructuring and complex morphology, no specific influence is recorded for the remaining two. An overall comparison demonstrates a significant reduction in adhesion on coarse cone‐shape patterns and complex microstructures. The specific adhesion mechanisms arising from biological morphologies may offer assistance to design bioinspired interfaces. Abstract : Adhesion mechanics investigation is carried on elastomeric replicas of natural leaf surfaces (decorated with complex hierarchical microstructures) using a modified ultra‐nanoindenter equipped with an original in situ real‐contact visualization system. The study presents original insights on force‐dependent adhesion behaviors associated to morphology dependent attachment–detachment modes, which may offer a valuable basis for designing bioinspired functional surfaces.